Cost-effectiveness of camrelizumab plus rivoceranib for advanced hepatocellular carcinoma in the context of regional disparities in China - Zhao, Zhonghua; Jiang, Xiongying; Wen, Shiping; Hao, Yanzhang (Frontiers in Oncology, 2024)
ObjectiveTo assess the cost-effectiveness of combining camrelizumab with rivoceranib versus sorafenib as initial treatment options for advanced hepatocellular carcinoma (HCC) across different developmental regions in China.MethodsUtilizing TreeAge Pro and data from the phase III randomized CARES-310 clinical trial, a model based on Markov state transitions was developed. Health state utility values were derived from the CARES-310 trial, and direct medical costs were obtained from relevant literature and local pricing data. The primary outcome measured was the incremental cost-effectiveness ratio (ICER), defined as the cost per additional quality-adjusted life year (QALY) gained per person. The ICERs were compared against the willingness-to-pay (WTP) thresholds of different regions in China, including low-income ($16,426.80), medium-income ($34,319.01), and high-income regions ($81,036.63). Sensitivity analyses were also conducted to assess the robustness and reliability of the model under various assumptions. A tornado diagram was used to illustrate the impact of parameter variations on the model’s cost-effectiveness.ResultsFor base case analysis, QALYs per person for the cohort receiving sorafenib were 0.91, with a corresponding cost of $8,860.97. For the cohort receiving camrelizumab plus rivoceranib, the QALYs per person were 1.71, with a corresponding cost of $16,190.72. The camrelizumab plus rivoceranib treatment group exhibited an increase of 0.80 QALYs and an additional expenditure of $7,329.75. The calculated ICER was $9,150.75 per QALY, which is below the WTP thresholds for all regions in China. The camrelizumab plus rivoceranib regimen is regarded as highly cost-effective in medium-income areas of China, with a probability of 99.9%. In high-income regions, the probability reaches 100.0%. Even in low-income regions, this regimen is considered 95.6% cost-effective. Sensitivity analysis further verified that these findings were robust across various assumptions.ConclusionThe combination of camrelizumab and rivoceranib as a treatment strategy not only improves health outcomes but also represents a cost-effective option across different developmental regions in China.